Green synthesis and characterisation of CuNPs: insights into their potential bioactivity. Issue 3 (14th February 2018) - Saran, Mukesh; Vyas, Swati; Mathur, Manas; Bagaria, Ashima
Abstract : The current investigation involves the green synthesis of copper nanoparticles (CuNPs) from an aqueous plant extract of Moringa oleifera Lam by two methods: (I) time‐based approach and (II) heat treatment of aqueous solution. Prepared CuNPs were characterised via Fourier transform infrared spectroscopy, X‐ray diffraction, scanning electron microscopy and transmission EM. The study also reveals the potential bioactivity of the prepared CuNPs. In vitro anti‐microbial efficiency of CuNPs was estimated against bacterial and fungal strains by the agar well diffusion method. Anti‐oxidant capacity of CuNPs was determined using ferric reducing ability of plasma (FRAP), lipid peroxidation (LPO) and peroxidase assays, while the antiplatelet potential was determined by measuring two haemostatic parameters (PT & APTT assay). The minimum inhibitory concentration was observed at 60 µg/ml against Streptomyces griseus and Aspergillus niger when NPs were prepared by method II. CuNPs prepared by the method I showed higher FRAP and LPO activities, while increased POX activity was found in CuNPs prepared by method II. CuNPs prepared using method I also showed better anti‐oxidant and antiplatelet potential. It was observed that M. oleifera ‐derived CuNPs exhibits strong anti‐microbial, anti‐oxidant and APTT potential. This indicates potential utilization of green synthesized NPs for various industrial and therapeutic strategies.